Assessing contract solutions for agricultural public goods in the Netherlands - Kina S. Harmanny; Peter Verburg; Catharina Schulp (International Journal of Agricultural Sustainability, 2025)
Farming significantly influences public goods (PGs) like water quality and biodiversity, both positively and negatively. Balancing sustainable PG delivery with short-term profitability is challenging. This study examines agri-environmental contracts in the Netherlands through a web-based search of grey literature. We gathered data on 137 agri-environmental contracts, reporting on PG delivery 294 times. The PG biodiversity was reported most frequently to be targeted by contracts (40%) followed by the PG agricultural landscapes and recreation (15%). We found various actors involved, particularly private ones, who are underrepresented in the literature and need more attention. Contrary to the preference for result-based contracts, 48% is input-based. In 68% of cases, monetary payments motivate participation, but tools like knowledge sharing are also reported. In 25% of the contracts, monitoring of results was not reported and effects on PG delivery were barely described. Furthermore, unexpected positive or negative spill-over effects of management practices on different PGs are not considered, risking counter effective outcomes. This study provides the first comprehensive national-level overview of contracts identifying current uptake of contracts and gaps therein, revealing a clear discrepancy between contract status and recent research on the topic. A better understanding of contract characteristics is vital for effective PG delivery in agriculture.